Implementasi Metode Service Quality Untuk Mengukur Tingkat Kepuasan Mahasiswa Terhadap Pelayanan Fakultas Ilmu Komputer - Zashosudi Shoranto; Jusuf Wahyudi; Rizka Tri Alinse (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Higher education demands the provision of quality academic services to ensure user satisfaction, specifically student satisfaction. The Faculty of Computer Science (Filkom) at Dehasen University, Bengkulu, does not yet have a measurable system for evaluating its service quality, making it difficult to identify areas for improvement based on student feedback. This study aims to implement the Service Quality (ServQual) method to measure student satisfaction with Filkom's academic services. The ServQual method is used to analyze the gap between student perceptions and expectations across five service quality dimensions: tangibles, reliability, responsiveness, assurance, and empathy.The results of the ServQual analysis indicate that overall, students are dissatisfied with the services provided. All dimensions and indicators received negative gap scores, with the Responsiveness dimension recording the largest gap. The conclusion of this study is that the ServQual method is effective as an objective service quality measurement tool. The developed application not only provides a comprehensive overview of student satisfaction levels but also serves as an efficient monitoring tool for the faculty to implement continuous improvement.